Non-uniform node deployment with mobile sink for wireless multimedia sensor networks - Yongyi Liu; Huiyong Yuan (2014 International Conference on Information Science, Electronics and Electrical Engineering, 2014)
Because of the high energy demands of multimedia data, the transmission of raw data collected at sensor nodes consumes a large amount of energy. The nodes closest to the sink tend to deplete their energy faster than other nodes, which is known as energy-hole problem. To address this problem, we first study the mobile sink model, and conclude the best mobility strategy. We then consider jointly sink mobility and node deployment, and formulate optimization problems that maximize the network lifetime subject to energy depletion balance. Finally, we propose a non-uniform node deployment strategy for periodical data gathering in multimedia sensor networks. Simulation experiments show that the proposed deployment strategy outperforms random deployment better scalability and longer network lifetime.